Creation of a Patient safety Culture in İntensive Care Units: Nurses' View to the Medical Errors - Nehir Somyürek; Esra Uğur (Association of Nurse Managers, 2016)
INTRODUCTION: As a descriptive study, this study was carried out among the nurses who are working in intensive care unit. Its aim is to indicate these nurses' opinions and approaches about medical errors threatening patient safety in a training and research hospital. METHODS: Sample of the descriptive study was formed by 99 nurses working in intensive care units (medical and surgical, cardiac surgery, cardiology, brain surgery, neonatal, and reanimation). Data were collected by data collection tool prepared by the investigators. The results were analysed with SPSS 15.0. The number of cases, percentage, and Chi-Square were used for the evaluation of the data. RESULTS: It is indicated that 89.9% of the nurses are trained about patient safety, 51.5% of them think that medical errors frequently are performed by physicians, 59.6% of them trust their knowledge and awareness to prevent errors. 72.7% of the nurses reported that they witnessed at least one case threatening patient safety during their professional life. 38.7% of them expressed that they reported these errors to the primary physician of the patient and 81.6% of them did not complete a written report in the last year. DISCUSSION AND CONCLUSION: Providing regular education not only for nurses but also for all healthcare professionals, creating a non-punitive system for reporting errors in a safe way, and disseminating patient safety culture improving practices were recommended to prevent medical errors which threaten patient safety in intensive care units.